Perceived sources and coping mechanisms of stress among undergraduate Indian dental students - H V Amith; Audrey M D'Cruz; Tanu Srivastav; R Soumya; B K Sony; Subin P Thomas (Wolters Kluwer Medknow Publications, 2012)
Context: The dental profession is the most stressful of all the health professions, and this is true for all stages of the dental career, i.e., for established dentists, young dentists and dental students. Aim: To identify the various sources and coping mechanisms of stress as perceived by Indian undergraduate dental students. Settings and Design: Descriptive cross-sectional questionnaire study. Materials and Methods: A modified version of the self-administered dental environment stress (DES) questionnaire was used. The responses were based on a four-point Likert scale (1 = little, 2 = moderate, 3 = considerable and 4 = great). Statistical Analysis Used: Descriptive analysis was carried out for the study variables. Results: Examinations, short lunch breaks, relationships, not knowing the local language, competition for sports and cultural activities, counseling rounds, difficulty of getting patients, portion and quota completion were the highest stressors. Having friends, planning and problem solving were the methods adopted by most of the students to cope with stress. Conclusions: The undergraduate dental students in India had high levels of perceived stress. Academic and nonacademic perceived sources of stress should be considered in curriculum planning and in the working environment for dental education.